USING JOURNALING PROMPTS ON EMMO APPLICATION TO ENHANCE STUDENTS’ DESCRIPTIVE TEXT WRITING - Damayanti, Rizkina; Mutiarani, Mutiarani (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The objective of this study is to know the influence using journaling on EMMO application to enhance students’ descriptive text writing. This research was conducted in SMP Arraisiyah Pamulang, South Tangerang. The population of this research was 8th grade students and the sample was grade 8.2 consist of 37 students. The method of this study was quantitative method using pre-experimental design. To collect the data, the researcher used pre-test and post-test as an instrument that given to the students. The result score of the data concluded that the total score of students in pre-test were 2.352 with the average score was 63.57. The lowest score in pre-test were 36 and the highest score is 85. The total score of students in post-test were 2.963 with the average 80.08. The lowest score of post-test were 60 and the highest score were 95. The result showed that there was significant different between students’ pre-test and post-test scores. Also from the results of the t-test, the tcalculation obtained is higher than the ttable (17.198 > 2.028). It means that there is a significant change and effect in students' pre-test to students' post-test scores and using journaling prompts on the EMMO application can enhance students' descriptive text writing.